FAULT SEAL ANALYSIS IN SEPINGGAN CARBONATES SEQUENCES INTERVAL (SCS), MPT FIELD, SOUTH MAHAKAM, KUTAI BASIN - Pian Nopiana, Aa
The MPT field is situated between two fields, STP field to the southeast and the MND to the northwest. The Manpatu-1X exploration well which was drilled in 2021, discovered a sandstone reservoir within the Sepinggan Carbonate Sequence (SCS) above the main target, Seppinggan Deltaic Sequences (SDS). The siliciclastic reservoir within the SCS interval has not been adequately explored as a hydrocarbon target and has not been produced in either the STP or MND fields. The hydrocarbon discovery in the MPT field proves the existence of hydrocarbon accumulation in downthrown block. Understanding the characteristics of the EMPT fault, which separates the MPT field from the MND field, is crucial for future exploration efforts. Therefore, the approach of static fault analysis using the Shale Gouge Ratio (SGR) parameter is employed to comprehend the characteristics of this fault. Structural style in MPT field is transtensional type with negative flower structure. This structural style was controlled by Sepinggan strike slip (dextral) fault system. This fault was formed and active in lower Miocene (U15) and active until middle – late Miocene (U95-MF85). E-MPT fault seal has characteristics as follows; SGR maximum threshold 0.4 (40%) (leaking), maximum capillary pressure threshold ± 10.5 bar, permeability threshold for fluid to flow ± 0.024 mD, juxtaposition type is tend to fully juxtaposed that dominated by extrareservoir faults, throw maximum is 877.4m and throw minimum is 0 m which is fault tip in the north east area. The difference in hydrocarbon accumulation between the upthrown (MND) and downthrown (MPT) blocks is caused by the E-MPT fault seal. This is proved by juxtapositions influenced by a seal membrane. Based on the availability of the data, it can be concluded that E-MPT fault is a partially sealing fault, with 0.4 SGR as cut-off and can be a conduit for hydrocarbon migration to the upthrown block (STP) also as an effective seal which separate between compartement (MND and MPT)